The state of the environmental awareness of students from Poland, Slovakia and Ukraine - selected results = Stan świadomości środowiskowej studentów z Polski, Słowacji i Ukrainy - wybrane wyniki - Cynk, Karolina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the article was presented results of international researches about environmental consciousness. The project was realized in 2015. The main purpose of this article is to describe the level of environmental knowledge, values and attitudes among university students from Central Eastern Europe.
Keywords: environmental awareness; state of the natural environment; sociological research; sociology of the environment; świadomość środowiskowa; stan środowiska przyrodniczego; badania socjologiczne; socjologia środowiska